The Study of Rice Potential Production on Sungai Ular Irrigation Fields in Pegajahan District Serdang Bedagai Regency - Rossiana Sianturi; Sumono Sumono; Saipul Bahri Daulay (Universitas Sumatera Utara, 2014)
Serdang Bedagai as one of rice centra region in North Sumatera with water source irrigation from irrigation Sungai Ular, need to be studied its wet rice fields irrigation network to hold out and increase production. The purpose of this research was to study the rice potential production on Sungai Ular irrigation fields in Pegajahan district, Serdang Bedagai regency in achieving the maximum level of rice production based on sun radiation level, time to grow rice, and rice varieties. This research also studied the ratio between irrigation field and crops field, the ratio between technical irrigation and pre technical and conventional irrigation and realibility of existing irrigation networks. In period of 2009-2013, the results indicated that the irrigation network realibility was good enough. The average ratio between technical irrigation and pre technical and conventional irrigation was 0,78, the average ratio between irrigation field and crops field was 1,75, and the rice production target was 59,86%. Keyword: Irrigation network, potential production, production target, rice.